Actin Family Proteins in the Human INO80 Chromatin Remodeling Complex Exhibit Functional Roles in the Induction of Heme Oxygenase-1 with Hemin - Takahashi, Yuichiro; Murakami, Hirokazu; Akiyama, Yusuke; Katoh, Yasutake; Oma, Yukako; Nishijima, Hitoshi; Shibahara, Kei-ichi; Igarashi, Kazuhiko; Harata, Masahiko (Frontiers in Genetics, 2017)
Nuclear actin family proteins, comprising of actin and actin-related proteins (Arps), are essential functional components of the multiple chromatin remodeling complexes. The INO80 chromatin remodeling complex, which is evolutionarily conserved and has roles in transcription, DNA replication and repair, consists of actin and actin-related proteins Arp4, Arp5, and Arp8. We generated Arp5 knockout (KO) and Arp8 KO cells from the human Nalm-6 pre-B cell line and used these KO cells to examine the roles of Arp5 and Arp8 in the transcriptional regulation mediated by the INO80 complex. In both of Arp5 KO and Arp8 KO cells, the oxidative stress-induced expression of HMOX1 gene, encoding for heme oxygenase-1 (HO-1), was significantly impaired. Consistent with these observations, chromatin immunoprecipitation (ChIP) assay revealed that oxidative stress caused an increase in the binding of the INO80 complex to the regulatory sites of HMOX1 in wild-type cells. The binding of INO80 complex to chromatin was reduced in Arp8 KO cells compared to that in the wild-type cells. On the other hand, the binding of INO80 complex to chromatin in Arp5 KO cells was similar to that in the wild-type cells even under the oxidative stress condition. However, both remodeling of chromatin at the HMOX1 regulatory sites and binding of a transcriptional activator to these sites were impaired in Arp5 KO cells, indicating that Arp5 is required for the activation of the INO80 complex. Collectively, these results suggested that these nuclear Arps play indispensable roles in the function of the INO80 chromatin remodeling complex.